2004
DOI: 10.1097/00006454-200404000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Use of ciprofloxacin in neonatal sepsis: lack of adverse effects up to one year

Abstract: Treatment of neonatal sepsis with ciprofloxacin resulted in no short term hematologic, renal or hepatic adverse effects and did not appear to be associated with clinical arthropathy or growth impairment at 1 year follow-up evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 24 publications
1
25
0
2
Order By: Relevance
“…Ciprofloxacin has a complex safety profile. A range of adverse drug reactions, including arthropathies, without identified long-term effects, need to be balanced with its efficacy (14)(15)(16). Potential neuroprotective effects were demonstrated in a juvenile animal model subjected to Escherichia coli sepsis (17).…”
Section: Discussionmentioning
confidence: 99%
“…Ciprofloxacin has a complex safety profile. A range of adverse drug reactions, including arthropathies, without identified long-term effects, need to be balanced with its efficacy (14)(15)(16). Potential neuroprotective effects were demonstrated in a juvenile animal model subjected to Escherichia coli sepsis (17).…”
Section: Discussionmentioning
confidence: 99%
“…It also did not appear to be associated with clinical arthropathy or growth impairment at 1-year follow-up. 21 Ciprofloxacin has been seen to be independently protective against ESBL K. pneumoniae colonisation (OR 0.1, 95% CI 0.0-0.97), in contrast with vancomycin (OR 6.6, 95% CI 1.73-25.28), amphotericin B (OR 12.0, 95% CI 1.79-80.5) and metronidazole (OR 5.3, 95% CI 1.1-25.6). 22 Moreover, fluoroquinolones can also reduce the current dependence on carbapenem agents and limit the potential for further emergence of carbapenem resistance.…”
Section: Discussionmentioning
confidence: 99%
“…One study involving 10 lactating women who were given ciprofloxacin in 3 doses every 12 h estimated that an infant fed only by breast would receive a maximum of 0.57 mg/kg daily dose of the drug. The dosage that an infant would receive is low compared to the levels used to treating newborn infants (10 to 40 mg/kg) [99][100][101][102] . Another study showed that an infant nursing from a woman being treated with ciprofloxacin for 10 d had no measurable ciprofloxacin in the infant's serum (< 30 μg/L) 2.7 h after breastfeeding [103] .…”
Section: Pregnancymentioning
confidence: 99%